2012
DOI: 10.15580/gjss.2012.6.102512154
|View full text |Cite
|
Sign up to set email alerts
|

Family Size, Income and Marriage Types as Predictors of Healthy Living: A Case Study of Families in Ogun State

Abstract: The study investigated the influence of family size, income and marriage types of healthy life of randomly selected families. It adopted ex-post-factor research design within Ikenne Local Government Area of Ogun State. Four hypotheses were tested and analyzed by the use of multiple regression and independent t-tests. All hypotheses were tested at 0.05 level of significant. The finding reveals that the three independent variables contributed 28.1% to healthy living and they were significant. Also family income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…For example, Hossain et al, (2003) in Bangladesh reveals that the adoption of improved varieties of rice has a positive impact on the richer households but had a negative effect on the poor, Dontsop-Nguezet et al (2011);Kijima et al, (2008);Diagne (2006) studies on the impact of New Rice for Africa (NERICA) in Nigeria, Uganda and Cote d'Ivoire also found that the adoption of NER-ICA has a positive and significant influence on farmers welfare, poverty reduction and yield respectively. Likewise, Mendola (2007) and Adeoye et al (2012) adopting the Propensity Score Matching (PSM) method and Local Average Treatment Effect (LATE) respectively confirmed the positive effect on household wellbeing arising from the impact of agricultural technology adoption on productivity and rural rice farmers' welfare in Bangladesh and Nigeria respectively.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Hossain et al, (2003) in Bangladesh reveals that the adoption of improved varieties of rice has a positive impact on the richer households but had a negative effect on the poor, Dontsop-Nguezet et al (2011);Kijima et al, (2008);Diagne (2006) studies on the impact of New Rice for Africa (NERICA) in Nigeria, Uganda and Cote d'Ivoire also found that the adoption of NER-ICA has a positive and significant influence on farmers welfare, poverty reduction and yield respectively. Likewise, Mendola (2007) and Adeoye et al (2012) adopting the Propensity Score Matching (PSM) method and Local Average Treatment Effect (LATE) respectively confirmed the positive effect on household wellbeing arising from the impact of agricultural technology adoption on productivity and rural rice farmers' welfare in Bangladesh and Nigeria respectively.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The empirical finding however contradicts a study by Amao and Awoyemi (2008) on adoption of improved cassava varieties by farmers in Osogbo, Osun State of Nigeria which indicated that marital status is not a significant determinant of adoption of improved cassava varieties. The increase in the probability of adopting improved cassava varieties by marital status may be due to the fact that marriage increases a farmer's concern for household welfare and food security which is therefore likely to have a positive effect on their decision to adopt improved agricultural technology (Johnson et al 2006;Adeoye et al 2012;Nnadi and Akwiwu, 2008). Also, the significant positive coefficient of access to improved cassava cutting (p < 0.1) attests to its influence on the adoption of improved cassava varieties by farmers.…”
Section: Determinants Of Adoption Of Improved Cassava Varietiesmentioning
confidence: 99%
“…For example, [23,24,25] studies on the impact of improved cassava technologies in Nigeria, Uganda and Cote d'Ivoire also found that the adoption of cassava improved technology has a positive and significant influence on farmers welfare, poverty reduction and yield respectively. Likewise, [26,27] adopting the Propensity Score Matching (PSM) method and Local Average Treatment Effect (LATE) respectively confirmed the positive effect on household wellbeing arising from the impact of agricultural technology adoption on productivity and rural cassava farmers' welfare in Bangladesh and Nigeria respectively. Adoption of agricultural technologies, such as the high yielding varieties could lead to significant increases in agricultural productivity and stimulate the transition from low productivity subsistence agriculture to a high productivity agro-industrial economy [28].…”
Section: Introductionmentioning
confidence: 89%
“…For example, in Bangladesh reveals that the adoption of improved varieties of cassava has a positive impact on the richer households but had a negative effect on the poor, [14,15,16] studies on the impact of improved cassava technologies in Nigeria, Uganda and Cote d'Ivoire also found that the adoption of cassava improved technology has a positive and significant influence on farmers welfare, poverty reduction and yield respectively. Likewise, [17,18] adopting the Propensity Score Matching (PSM) method and Local Average Treatment Effect (LATE) respectively confirmed the positive effect on household wellbeing arising from the impact of agricultural technology adoption on productivity and rural cassava farmers' welfare in Bangladesh and Nigeria respectively. Adoption of agricultural technologies, such as the high yielding varieties could lead to significant increases in agricultural productivity and stimulate the transition from low productivity subsistence agriculture to a high productivity agro-industrial economy [19].…”
Section: Introductionmentioning
confidence: 89%